Aminoetoxivinilglicina na qualidade e maturação de melão cantaloupe em condições tropicais. - Lourenço, Isabel Peixoto (2013)
Increased retention of climacteric fruits occurs by inhibiting the synthesis or action of ethylene in order to delay ripening. One way to control this process may be the application of plant growth regulators such as aminoethoxivinilglicin (AVG), an inhibitor of ethylene biosynthesis. AVG prevents the formation of autocatalytic ethylene reduces respiration climacteric fruit abscission and increases firmness when sprayed on fruit trees before the harvest. This study aimed to evaluate the effect of AVG on ripening and fruit quality of muskmelon cantaloupe in greenhouse and field. The experimental design was completely randomized, with a 3 x 5, with three dates of application and five doses of the active ingredient for the two experiment, being used two replicates, with eight plants per replication at planting in a greenhouse and three replicates of five fruits formed in field. The responses were specific for each environment and in a greenhouse using AVG influences the quality of melons, as the fruit size and internal cavity; does not change the content of soluble solids, total sugars and firmness regardless of dose and application of the product and influences the maturation of melon fruits for increasing the permanence the fruit to the plant when sprayed two or three times at a dose of 270 mg. L-1. Under field conditions the AVG influences the quality of the melon fruit, providing larger fruits with internal cavity smaller, higher soluble solids content and firmness and influences the maturation promoting greater permanence of fruit on the plant. Therefore, AVG influenced the quality and maturity of melon fruits under both culture conditions.